An undergraduate educational model for developing sustainable nursing practice: A New Zealand perspective. (February 2018) - Collins, Emma; Ross, Jean; Crawley, Josie; Thompson, Raeleen
Abstract: In this article we reflect on the concept of sustainability and in particular, sustainability within our undergraduate nursing programme. Given the complexity of global environmental change and the prediction that this will impact on health, nurses need to be responsive, knowledgeable and prepared to act on these changes (Anåker and Elf, 2014). Therefore as nurse educators we are responsible for ensuring that undergraduate nursing students are prepared for this reality. Sustainability is a relatively new concept emerging in the discipline of nursing. It is a multifaceted concept embedded within a systems framework, influenced by international, national and local factors. The concept of sustainability can be difficult to articulate and to evidence in daily nursing practice. Student nurses at the School of Nursing, Otago Polytechnic, Dunedin, are expected to meet the graduate profile indicating that they are a sustainability-practicing graduate on completion of their degree programme. As faculty staff, we have been encouraged to explore the concept of sustainability and how it relates to nursing practice. An in-depth review of the international literature, engagement of faculty colleagues, development of frameworks, and mapping of the educational content within the Bachelor of Nursing programme, has led us to develop a model for conveying and teaching sustainable practice. Highlights: Sustainability is a relatively new concept in nursing, influenced by international, national and local factors. Sustainability can be difficult to articulate and evidence in daily nursing practice. Sustainable nursing graduates are developed through a revised BN curriculum. A robust debate amongst the discipline must occur to ensure that sustainable nursing practice is progressed.